The law and economics of antidiscrimination law - Donohue, John J. 1953- (National Bureau of Economic Research, 2005)
"This essay provides an overview of the central theoretical law and economics insights concerning antidiscrimination law across a variety of contexts including discrimination in labor markets, housing markets, consumer purchases, and policing. The different models of discrimination based on animus, statistical discrimination, and cartel exploitation are analyzed for both race and sex discrimination. I explore the theoretical arguments for prohibiting private discriminatory conduct and illustrates the tensions that exist between concerns for liberty and equality. I also discuss the critical point that one cannot automatically attribute observed disparities in various economic or social outcomes to discrimination, and illustrate the complexities in establishing the existence of discrimination. The major empirical findings showing the effectiveness of federal law in the first decade after passage of the 1964 Civil Rights Act are contrasted with the generally less optimistic findings from subsequent antidiscrimination interventions"--National Bureau of Economic Research web site.
Keywords: Recht; Discrimination in employment -- United States; Discrimination in housing -- United States; Race discrimination -- Economic aspects -- United States; Race discrimination -- Law and legislation -- United States; USA